1975
DOI: 10.1063/1.88231
|View full text |Cite
|
Sign up to set email alerts
|

Surface stress and the normal mode of vibration of thin crystals :GaAs

Abstract: The normal mode of vibration of (111) GaAs wafers with a thickness below about 15 μm was found to depend strongly on the surface preparation and on the ambient atmosphere. This dependence was attributed to effects directly related to the surface stress σs. It was shown that σs can be evaluated from the natural frequency of vibration. The values of σs, in the 〈110〉 direction, for etched and unetched (111) GaAs wafers in room atmosphere were found to be 325 and 570 dyn/cm, respectively. It was further demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
84
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 2 publications
1
84
0
Order By: Relevance
“…In his model, the effect of residual surface stress is represented by a compressive axial force. Gurtin et al 8 modified this model by applying in addition to the compressive axial force, a distributed traction over the beam surfaces induced by the residual surface tension under bending and concluded that surface elasticity influences the natural frequency of microbeams while residual surface stress does not have any significant effect, in contrast to the results of Lagowski et al 7 The surface/interface tension of fluids can be expressed by the Laplace-Young equation. Gurtin et al 9 formulated a continuum model of surface elasticity in which the LaplaceYoung equation which was extended to solid materials.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…In his model, the effect of residual surface stress is represented by a compressive axial force. Gurtin et al 8 modified this model by applying in addition to the compressive axial force, a distributed traction over the beam surfaces induced by the residual surface tension under bending and concluded that surface elasticity influences the natural frequency of microbeams while residual surface stress does not have any significant effect, in contrast to the results of Lagowski et al 7 The surface/interface tension of fluids can be expressed by the Laplace-Young equation. Gurtin et al 9 formulated a continuum model of surface elasticity in which the LaplaceYoung equation which was extended to solid materials.…”
mentioning
confidence: 74%
“…[4][5][6] Therefore, it has been a great theoretical, computational, and experimental activity that has permitted a better understanding of the stress effects on surface physics. Lagowski et al 7 analyzed the natural frequency of microbeams by considering the influence of the residual surface stress on the normal mode of vibration of thin crystals. In his model, the effect of residual surface stress is represented by a compressive axial force.…”
mentioning
confidence: 99%
“…The finite-size effects have been the subject of theoretical studies for the past years. [2][3][4][5][6][7][8] In experimental work on single-crystalline Si cantilevers it has been shown that the Young's modulus strongly depends on the thickness. 9 This behavior has also been observed for suspended crystalline silver nanowires.…”
mentioning
confidence: 99%
“…By solving this inverse problem, we actually provide a viable experimental method to determine the effects of both surface elasticity and surface stress. Because the surface stress effect is modelled as an axial load on the structure, two different models arise: the concentrated load model [3][4][5][6][7][8]13,16,24,[35][36][37] and the distributed load model [35][36][37]. The difference between these two models is also discussed.…”
Section: Introductionmentioning
confidence: 99%
“…By the thermodynamics definition, τ is a tensor associated with the reversible work to elastically stretch a pre-existing surface [15]. We see that τ consists of two parts: σ and C s ; σ , which is strain independent, is often referred to as surface stress [16][17][18]; C s , which is strain dependent, is often referred to as surface elasticity [17][18][19]. Surface elasticity is due to the formation of a surface layer that has a different elastic surface stress have different impacts on different resonant frequencies.…”
Section: Introductionmentioning
confidence: 99%